Physicians’ pain management confidence versus competence - Douglass, PharmD, Mark A.; Sanchez, PharmD, BCPS, Gail M.; Alford, MD, MPH, Daniel P.; Wilkes, RNC, MS, AOCN, Gail; Greenwald, MD, Jeffrey L. (Journal of Opioid Management, 2018)
Objective: To assess awareness of existing pain management guidelines and compare physicians’ confidence versus competence in selected pain management skills. Design: Prospective survey study. Setting: A large urban tertiary medical center. Patients, participants: All Department of Medicine interns, senior residents, and attending physicians were sent a questionnaire; the overall response rate was 30 percent (91/304). Interventions: The questionnaire assessed physicians’ awareness of the institution’s pain management guidelines, their self-reported comfort level (confidence) with, and a knowledge assessment (competence) of three pain management skills (managing chronic-continuous pain, equianalgesic dose conversion, and managing breakthrough pain) using validated, standardized case vignettes. Main outcome measures: A comparison of physicians’ confidence with their competence in these pain management skills. Results: A total of 23 percent (21/91) of the respondents reported an awareness of the institution’s pain management guidelines. Interns were significantly less confident than senior residents in all three pain management skills (p < 0.001, 0.006, 0.02) but nonsignificantly more competent in two of three skills (chronic-continuous pain, dose conversion). Attendings were generally more confident and nonsignificantly more competent than senior residents in all three pain management skills. Conclusions: The underutilization of the pain management guidelines illustrates that the mere existence of these resources as a means of ensuring optimal pain management is insufficient. Creative pain management educational initiatives are needed to address the disparity between physician confidence and competence.